2019
DOI: 10.1021/acs.chemrestox.9b00058
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphorus Flame Retardants Impair Intracellular Lipid Metabolic Function in Human Hepatocellular Cells

Abstract: Organophosphorus flame retardants (OPFRs), a replacement for brominated flame retardants, have gradually been accepted as endocrine disrupting chemicals (EDCs). Recently, evidence has shown that these EDCs could cause chronic health problems, such as obesity, and referred to as metabolic disruptors. However, the disturbance to lipid metabolism caused by OPFRs remains poorly understood, especially at biological molecular levels. Herein, we used the human hepatocellular cells (HepG2) to study the lipid metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 48 publications
2
24
0
Order By: Relevance
“…Metabolomics studies the role of small-molecule metabolites in pregnancy and pregnancy-related diseases from a holistic perspective. It has been shown that different OPFRs cause the cellular metabolism disorder in different ways, including oxidative stress and the equilibrium of osmotic pressure, also caused mitochondrial dysfunction (17). In addition, cells exposed to OPFRs may also induce apoptosis through autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics studies the role of small-molecule metabolites in pregnancy and pregnancy-related diseases from a holistic perspective. It has been shown that different OPFRs cause the cellular metabolism disorder in different ways, including oxidative stress and the equilibrium of osmotic pressure, also caused mitochondrial dysfunction (17). In addition, cells exposed to OPFRs may also induce apoptosis through autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…The protein isolation, the protein concentration determination, and the Western blot were performed as in our previous reports (Hao et al, 2019). TLR2 and TLR4 antibodies were from ImmunoWay Biotechnologies (San Diego, California, USA).…”
Section: Protein Isolation and Western Blotmentioning
confidence: 99%
“…The probes did not label all of these targets in the same manner (Figure 5), indicating selectivity for some proteins depending on probe structure and reactivity. Given the importance of lipases and lipid signaling in brain, [49][50][51] the effects of OPs on lipid metabolism has been proposed as a major contributing factor to the long-term negative impacts of OP exposure on development and cognitive function. 52 Our OP ABPs represent new tools for profiling these important enzymes in the brain and other tissues that react with different OP structures.…”
Section: Impacts Of Organophosphates On Lipid Metabolismmentioning
confidence: 99%